The Festival of Every Day: Philo and Seneca on Quotidian Time - Kattan Gribetz, Sarit (Harvard theological review, 2018)
In Book Two of De Specialibus Legibus (Special Laws), Philo of Alexandria presents his readers with a “festival manual”: a list of ten holidays, their origins, and the practices associated with each one. Philo names the first festival in his list ἡμέρα πσα, “every day,” about which he muses: “If all the forces of the virtues remained unvanquished throughout, then the time from birth to death would be one continuous feast.” In what historical, intellectual, and literary context might we best understand Philo's “every day festival”? And how can we understand Philo's view of quotidian time in the context of his conception of time and temporality more generally? In this paper, I argue that Philo's presentation of this festival of the every day, and, more generally, his perspective on daily time, is an engagement not only with biblical texts but also with contemporaneous Stoic perspectives about time, especially those articulated by the philosopher Seneca the Younger. I thus read Philo's De Specialibus Legibus in conversation with Seneca's De Brevitate Vitae (On the Shortness of Life), analyzing their similar perspectives on daily time and suggesting several ways of understanding the connections between the two texts. I conclude by explaining how appreciating the similarities between Philo and Seneca's ideas about quotidian time also allows us better to understand Philo's exposition of the other festivals, especially his presentation of the Sabbath.